Análise de viabilidade econômica de um empreendimento imobiliário sustentável - Trombeta, Fernando Moraes [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
This paper, whose purpose is to study the feasibility of building a sustainable house complex compared to a conventional one, begins approaching some of the history of sustainability, mentioning it's pillars and presenting some sustainable materials and techniques that the market can provide us already. In this project, the following materials and techniques were used: ecological brick, photovoltaic panels, rainwater harvesting system, green roof and the position of the building considering the insolation. This paper showed that the return on investment time is still very high in Brazil, a factor that can discourage the market to invest in this field

Este trabalho, que tem como propósito estudar a viabilidade de construção de um condomínio sustentável em relação a um convencional, se inicia abordando um pouco sobre a história da sustentabilidade, passando por seus pilares e apresentando alguns materiais e algumas técnicas sustentáveis presentes hoje no mercado. No projeto, foram utilizadas algumas iniciativas sustentáveis, como tijolo ecológico, placas fotovoltaicas, sistema de captação de águas pluviais, telhado verde e posicionamento da edificação em relação à insolação. Concluiu-se que atualmente o tempo de retorno do investimento ainda é muito elevado no Brasil, fator que pode desmotivar o mercado a movimentar este campo
Economic viability analysis of a sustainable real estate development
Keywords: Sustentabilidade; Viabilidade economica; Energia solar; Aguas pluviais; Sustainability